Bioaktivitas Antibakteri Lamun Thalassia hemprichii dan Enhalus acoroides - Arief Anthonius Purnama; Eti Meirina Brahmana (Universitas Andalas, 2018)
The objective of present study was to identify bioactivity of antibacterial Indonesian Seagrass Thalassia hemprichii dan Enhalus acoroides from Karang Tirta Beach, Padang City, West Sumatera. This is a preliminary research for a new alternative antibiotic from Seagrass in Indonesia. In this study the seagrass was examined by a maceration process and using the rotary evaporator to obtain viscous extract. The material for the bioactivity testing was performed upon several intended bacteria such as Escherichia coli, Stapillococcus aureus, and Bacillus subtilis. The bioactivity testing was performed by using the method of resazurin and MIC (Minimum Inhibitory Concentration), which is determined by looking at well blue-colored at the smallest concentration. The result revealed that the best antibacterial bioactivity of Thalassia hemprichii extract was a total of 62.50 μg/mL N-hexane solvent against Escherichia coli and Stapillococcus aureus bacteria. While the best antibacterial bioactivity of Enhalus acoroides extract is 15.62 μg/mL of N-hexane solvent against Stapillococcus aureus.